Naming Ability Changes in Physiological and Pathological Aging - Cotelli, Maria (Frontiers Research Foundation, 2012)
Over the last two decades, age-related anatomical and functional brain changes have been characterized by evidence acquired primarily by means of non-invasive functional neuroimaging. These functional changes are believed to favor positive reorganization driven by adaptations to system changes as compensation for cognitive decline. These functional modifications have been linked to residual brain plasticity mechanisms, suggesting that all areas of the brain remain plastic during physiological and pathological aging. A technique that can be used to investigate changes in physiological and pathological aging is non-invasive brain stimulation (NIBS). The present paper reviews studies that have applied NIBS in younger and older adults and in patients with dementia to track changes in the cerebral areas involved in a language task (naming). The results of this research suggest that the left frontal and temporal areas are crucial during naming. Moreover, it is suggested that in older adults and patients with dementia, the right prefrontal cortex is also engaged during naming tasks, and naming performance correlates with age and/or the degree of the pathological process. Potential theories underlying the bilateral involvement of the prefrontal cortex are discussed, and the relationship between the bilateral engagement of the prefrontal cortex and the age or degree of pathology is explored.